Bioinformatics analysis and prokaryotic expression of a cystatin analogue from Spirometra erinaceieuropaei - Lin Huang; Ling Mai; Gang Lv; Xinjun Chen (Biotechnology & Biotechnological Equipment)
Cystatin plays a crucial role in immune evasion by parasites. It regulates diverse immune response processes, such as antigen presentation, cytokine and NO production, and phagocytosis. In recent years, an increasing number of parasite cystatins have been identified and studied for the treatment of inflammatory diseases. In contrast, cystatin from Spirometra erinaceieuropaei has received limited research attention. The objective of this study was to utilize bioinformatics tools and molecular biology techniques to predict the biological properties and obtain a recombinant cystatin analogue from Spirometra erinaceieuropaei (SeCystatin). The SeCystatin gene consists of 417 bp and encodes a putative 100-amino acid protein. The predicted molecular weight and isoelectric point of SeCystatin were 10.89 kDa and 6.82, respectively; SeCystatin possesses 12 phosphorylation sites and five post-translational modification sites but has no signal peptide and transmembrane region. The secondary structure of SeCystatin consists of one α-helix, four β-folds and six coils. It also possesses a cystatin-specific conserved domain, QxVxG, which is positioned at the boundary between the first and second β-folds, thereby demonstrating the characteristic features of type I cystatin. In the context of molecular evolution, SeCystatin demonstrates the highest level of evolutionary similarity to Schistocephalus solidus. The SeCystatin gene was fully synthesized, and the recombinant plasmid pET-30a (+)-SeCystatin was constructed to express the target protein in Escherichia coli BL 21. Recombinant SeCystatin was successfully induced for expression by IPTG and subsequently purified using affinity chromatography (Ni-IDA). Our study provides a solid foundation for further studies on the biological functions of SeCystatin.